2023
DOI: 10.3390/ma16155373
|View full text |Cite
|
Sign up to set email alerts
|

Development of Molecular Dynamics and Research Progress in the Study of Slag

Chaogang Zhou,
Jinyue Li,
Shuhuan Wang
et al.

Abstract: Molecular dynamics is a method of studying microstructure and properties by calculating and simulating the movement and interaction of molecules. The molecular dynamics simulation method has become an important method for studying the structural and dynamic characteristics of slag systems and can make up for the shortcomings of existing detection methods and experiments. Firstly, this paper analyzes the development process and application fields of molecular dynamics, summarizes the general simulation steps an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The RDF is expressed as the interaction distance and coordination number between atoms in the melt atomic cluster. 25 It is mainly used to analyze the bond length between atomic pairs and the distribution of surrounding atoms in the melt structure, which can reflect the average bond length between two particles and the changing tendency of bond formation. It is calculated using the following formula:where N i and N j are the number of particles i and j , r is the distance between particles i and j , and V represents the total volume of the system, respectively.…”
Section: Calculation and Experimental Methodsmentioning
confidence: 99%
“…The RDF is expressed as the interaction distance and coordination number between atoms in the melt atomic cluster. 25 It is mainly used to analyze the bond length between atomic pairs and the distribution of surrounding atoms in the melt structure, which can reflect the average bond length between two particles and the changing tendency of bond formation. It is calculated using the following formula:where N i and N j are the number of particles i and j , r is the distance between particles i and j , and V represents the total volume of the system, respectively.…”
Section: Calculation and Experimental Methodsmentioning
confidence: 99%
“…Since the 21st century, molecular dynamics simulation methods have gradually been introduced into the field of metallurgy. Research on molten slag is the most widely applied application of molecular dynamics in metallurgy [ 21 ]. Through molecular dynamics simulation, researchers have vividly defined the types of oxygen atoms, characterized the network structure, and depicted the evolution of atomic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of parameters like temperature or concentration gradients can be studied to achieve an efficient slag design, this mostly with respect to an optimal metal product. A recent review is found by Zhou et al [17]. MD simulations have been frequently used to obtain the short-range ordered structure of molten slags and the melt's kinetic characteristics [18,19].…”
Section: Introductionmentioning
confidence: 99%